Postcard to Max Bredig, June 19, 1917 (1917)
Postcard sent to Max Albert Bredig (1902-1977) wishing him a happy 15th birthday. The front of the postcard features a portrait of the Grand Ducal Family of Baden, the last ruler, Friedrich II, his wife Hilda of Nassau, and likely his mother, Grand Duchess Louise of Prussia. The card was issued for the "Badischer Opfertag" (Baden Sacrifice Day) on September 20, 1915, to raise funds for troops during World War I.
Keywords: Bredig, Max Albert, 1902-1977; World War (1914-1918); Portraits, Group; Nobility